Business ambience for implementing Just-in-sequence strategy – the automotive industry in Serbia: case study - Andjelković, Aleksandra; Milovanović, Goran; Milanović, Sandra; Stojanović, Dalibor (Journal of Business Economics and Management, 2025)
Persistent issues in the automotive industry – such as delivery delays and frequent stock-outs – indicate that the vision of perfectly synchronized flows of raw materials, parts, and components within complex industrial production and logistics systems remains a significant challenge. To mitigate demand variability and uncertainty, companies often maintain high levels of safety stock, which significantly increases costs and erodes competitiveness. At the same time, such supply chains are characterized by limited responsiveness, resulting in unfulfilled targets related to reduced lead times and reliable customer deliveries. As a response, supply chains in the automotive sector are increasingly opting for the implementation of Just-in-Sequence (JIS) strategies to ensure adaptation to diverse product requirements and cost savings, as well as enhance both responsiveness and efficiency. Within this context, the objective of this research is to identify key elements necessary for the successful implementation of the JIS strategy in an automotive company. The research findings reveal notable differences in the perceptions of employees from Production, Logistics, and Sales sectors regarding the importance of the analysed variables and the potential for implementing a JIS strategy.